2018
DOI: 10.1002/jcb.27638
|View full text |Cite
|
Sign up to set email alerts
|

Leucine aminopeptidase 3 promotes migration and invasion of breast cancer cells through upregulation of fascin and matrix metalloproteinases‐2/9 expression

Abstract: Overexpression of leucine aminopeptidase 3 (LAP3) is involved in proliferation, migration, and invasion of several tumor cells and plays a crucial role in tumor metastasis. However, the related mechanism remains unknown. In this study, we used MDA-MB-231 and MCF7 breast cancer cell lines to explore the role of LAP3 in the regulation of cancer cell migration and invasion by employing the natural LAP3 inhibitor bestatin and a lentivirus vector that overexpresses or knocks down LAP3. Bestatin inhibited tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 23 publications
(40 reference statements)
0
35
0
Order By: Relevance
“…Fang and colleagues just recently showed that LAP3 is involved in migration and invasion of breast cancer cells. 25 Accordingly, we demonstrated that knock down of LAP3 and DPP7 in D492HER2 cells reduced the positive activity of melflufen indicating that other aminopeptidases could play a role in breast cancer treatment, an important finding which needs further evaluation.When compared to the commonly used breast cancer drug doxorubicin we were able to show that melflufen is more potent both in vitro and in vivo. D492, D492HER2, and MDA-MB231 cell lines were more sensitive to melflufen than doxorubicin, both in monolayer and in 3D culture.…”
Section: F I G U R E 5 In Vivo Effects Ofmentioning
confidence: 78%
“…Fang and colleagues just recently showed that LAP3 is involved in migration and invasion of breast cancer cells. 25 Accordingly, we demonstrated that knock down of LAP3 and DPP7 in D492HER2 cells reduced the positive activity of melflufen indicating that other aminopeptidases could play a role in breast cancer treatment, an important finding which needs further evaluation.When compared to the commonly used breast cancer drug doxorubicin we were able to show that melflufen is more potent both in vitro and in vivo. D492, D492HER2, and MDA-MB231 cell lines were more sensitive to melflufen than doxorubicin, both in monolayer and in 3D culture.…”
Section: F I G U R E 5 In Vivo Effects Ofmentioning
confidence: 78%
“…LAP3 is also implicated in antigen and major histocompatibility complex class I peptide processing, and is associated with the proinflammatory effects of IFN-γ [32]. In cancer, LAP3 has also been linked to tumor cell proliferation, migration, and invasion [33,34]. Altered LAP3 expression has also been observed in esophageal squamous cell and hepatocellular carcinoma [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RUNX3 is involved in the regulation of epithelial-mesenchymal transition (EMT) by Evidence-Based Complementary and Alternative Medicine directly regulating the transcription of blocking protein-1, thus inhibiting tumor invasion and metastasis by protecting nesting apoptosis [22]. MMP-2 can break the degradation balance of matrix, induce cancer cells to penetrate the barrier formed by extracellular matrix and basement membrane, and reduce the adhesion between cells, so that cancer cells can infiltrate, invade, and metastasize to distant organs in surrounding tissues [23,24]. In the process of degradation, large amounts of vascular endothelial growth factors stored in the extracellular matrix can be released to induce tumor angiogenesis and provide the necessary nutritional basis and pathway for tumor cell invasion [25].…”
Section: Discussionmentioning
confidence: 99%